Enterprise management strategies in the era of cloud computing - Rao, N. Raghavendra 1939- (Advances in business information systems and analytics (ABISA) book series, 2015)
"This book seeks to explore the possibilities of business in the cloud, providing a cutting-edge look at the exciting and multifaceted relationships between cloud computing, software virtualization, collaborative technology, and business infrastructure in the 21st Century"--Provided by publisher.